Synthesis and characterization of aluminum or copper tungstophosphate and tungstosilicate immobilized in a polymeric blend - Fuchs, Vanesa Maria (2008)
Aluminum or copper tungstophosphates and tungstosilicates were synthesized and immobilized in a polymeric blend formed by polyvinyl alcohol and polyethylene glycol using the freeze-thawing method. The salts retained the Keggin structure of the heteropolyanions during their synthesis and immobilization. Materials with spherical shape and a mean size of 2 mm were obtained, with an almost constant distribution of the salts along the sphere width. Besides, the immobilized salts presented very strong acid sites and good thermal stability. The synthesized hybrid materials present suitable properties to be used as heterogeneous acid catalysts which are very attractive for many processes as replacement of conventional liquid ones. © 2008 Elsevier Ltd. All rights reserved.